Teaching engineering ethics: a necessary measure for engineering capacity building in Arab countries - Nasef, Mohamed Mahmoud; Faris, Waleed Fekry (Inderscience Publishers, 2010)
Interest in engineering ethics education has developed significant momentum in most of advanced countries unlike Arab countries, which have not yet paid enough attention to such critical issue. As engineering work becomes more complex and diverse an understanding of engineering ethics becomes as important to the proper education of engineers as their technical knowledge. This means that engineering students have to learn about their ethical obligations towards society, their employers, and themselves. This paper discusses the needs and reasons for integrating ethics into the education of undergraduate engineering students in Arab countries. Goals of teaching engineering ethics and various approaches for achieving these goals are also illustrated.